2023
DOI: 10.3390/cells12091250
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Brains from Subjects with Diabetes Mellitus Display Reduced GLUT4 Expression and Soma Area in Hippocampal Neurons: Potential Involvement of Inflammation

Abstract: Diabetes mellitus (DM) is an important risk factor for dementia, which is a common neurodegenerative disorder. DM is known to activate inflammation, oxidative stress, and advanced glycation end products (AGEs) generation, all capable of inducing neuronal dysfunctions, thus participating in the neurodegeneration progress. In that process, disturbed neuronal glucose supply plays a key role, which in hippocampal neurons is controlled by the insulin-sensitive glucose transporter type 4 (GLUT4). We investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…These data ascribe the hippocampal GLUT4 protein the same functional role it plays in the classic insulin-sensitive tissues [40], placing the transporter as a key player in the hippocampal metabolic glucose utilization. Additionally, we and others have already described GLUT4 in hippocampal neurons of the human brain, where it seems to play an important role under pathological conditions, as further discussed [74][75][76].…”
Section: Glucose Transport and Transporters In The Hippocampusmentioning
confidence: 57%
See 3 more Smart Citations
“…These data ascribe the hippocampal GLUT4 protein the same functional role it plays in the classic insulin-sensitive tissues [40], placing the transporter as a key player in the hippocampal metabolic glucose utilization. Additionally, we and others have already described GLUT4 in hippocampal neurons of the human brain, where it seems to play an important role under pathological conditions, as further discussed [74][75][76].…”
Section: Glucose Transport and Transporters In The Hippocampusmentioning
confidence: 57%
“…This observation indicates that inflammation is an important mechanism for neurodegeneration during the health-T2D transition. Additionally, no alterations in the immunoreactivity for carboxymethyllysine (a marker of AGE activity) was observed in hippocampal CA4 neurons from obese or obese diabetic subjects [76].…”
Section: Ad Dm and Glut4 In The Hippocampusmentioning
confidence: 89%
See 2 more Smart Citations
“…Moreover, hyperglycemia by modulating the expression of glucose transporters induces neuronal insulin resistance [ 60 ]. In the brains of AD patients, a significant reduction in the expression of GLUT1, GLUT3, and GLUT4 was observed, impacting neuronal activity [ 61 ], progressive neuronal loss, and neurodegeneration [ 58 , 62 ]. Intriguingly, in our study, we observed that TIR treatment prevented the HG induced mRNA and protein downregulation of GLUT3 along with GLUT1, GLUT4, and SORBS1, a protein that takes part in diabetes pathogenesis [ 31 ], and regulates GLUT4 translocation [ 32 ] affecting neuronal insulin resistance [ 63 ].…”
Section: Discussionmentioning
confidence: 99%